Spatial Distribution and Contamination Assessment of Heavy Metals in Surface Sediments of the Caofeidian Adjacent Sea after the Land Reclamation, Bohai Bay - He Zhu; Haijian Bing; Huapeng Yi; Yanhong Wu; Zhigao Sun (Journal of Chemistry)
Land reclamation can significantly influence spatial distribution of heavy metals in inshore sediments. In this study, the distribution and contamination of heavy metals (Cd, Cr, Cu, Ni, Pb, and Zn) in inshore sediments of Bohai Bay were investigated after the land reclamation of Caofeidian. The results showed that the concentrations of Cd, Cr, Cu, Ni, Pb, and Zn in the sediments were 0.20–0.65, 27.16–115.70, 11.14–39.00, 17.37–65.90, 15.08–24.06, and 41.64–139.56 mg/kg, respectively. These metal concentrations were generally higher in the area of Caofeidian than in other Chinese bays and estuaries. Spatially, the concentrations of Cd, Cr, Cu, Ni, and Zn were markedly lower in the sediments close to Caofeidian compared with other regions, whereas the concentrations of Pb showed an opposite case. Hydrodynamic conditions after the land reclamation were the major factor influencing the distribution of heavy metals in the sediments. Grain sizes dominated the distribution of Cu and Zn, and organic matters and Fe/Mn oxides/hydroxides also determined the distribution of the heavy metals. Multiple contamination indices showed that the inshore sediments were moderately to highly contaminated by Cd and slightly contaminated by other heavy metals. Similarly, Cd showed a high potential ecorisk in the sediments, and other metals were in the low level. Chromium contributed to higher exposure toxicity than other metals by the toxicity unit and toxic risk index. The results of this study indicate that after the land reclamation of Caofeidian the contamination and ecorisk of heavy metals in the sediments markedly decreased in the stronger hydrodynamic areas.